Negotiating Norms - Ng, J (2018)
This thesis examines the practice of normative contestation in the African Union (AU) and Association of Southeast Asian Nations (ASEAN). Dissatisfied with existing liberal, realist, and rationalist accounts of normative change, the thesis develops a new theoretical approach involving competing 'norm circles,' actors committed to endorsing or enforcing a norm, whose perceived utility of a norm determines their stance. The model suggests that under conditions of contestation involving at least two norm circles, actors compete according to the terms of their domain, the regional organization. The differences involve actors' competencies in controlling the initiative, their mastery of other shared norms, and their ability to seek other opportunities of influence, termed 'metis.' Empirically, the thesis examines six case studies, three each from the AU and ASEAN, in which significant new norms testing member state sovereignty were proposed, after which the norms were either accepted, rejected, or qualified, according to how the contest unfolded. Each case reviews the historical origins of the norm and the proposal, followed by analysing how each norm circle used the factors mentioned above to seek approval for their proposals. It then assesses the relative importance of the factors, alternative explanations, and future implications for the norms in each case. In the AU, the three cases were the proposals for the United States of Africa, the Conference on Security, Stability, Development and Cooperation in Africa, and the Pan-African Parliament. In ASEAN, the thesis examines the question of human rights in the ASEAN Charter, the attempt to formalize the 'ASEAN minus X' principle, also during the charter drafting, and the contestation over the creation of a regional human rights mechanism, which eventually became the ASEAN Intergovernmental Commission on Human Rights.